Tectonics of the Hjort region of the Macquarie Ridge Complex, southernmost Australian-Pacific plate boundary, southwest Pacific Ocean - Meckel, Timothy Ashworth (2003)
text The Hjort Ridge, Trench, and Plateau comprise the southernmost portion of the Macquarie Ridge Complex (MRC), the Australian-Pacific plate boundary south of New Zealand. The MRC is an ideal location to study deformation and structural development at an obliquely convergent plate boundary involving oceanic lithosphere. This dissertation documents structures and processes in the Hjort region associated with incipient subduction, an outstanding problem in plate tectonics. I investigated the evolution of the plate boundary from ~33 Ma to the present day, concentrating on the active and recent structural development. Interpretations are based on analyses of recently collected geophysical data in the Hjort region, including swath bathymetry, reflectivity, seismic reflection, gravity, magnetics, and seismicity. The Australian plate is actively underthrusting the Pacific plate along the Hjort Trench, but self-sustaining subduction does not appear to have commenced. Transpression along the length of the plate boundary has been accomodated by lithospheric flexure, strike slip faulting, and geographically limited underthrusting. A consistent relationship exists between the convergence angle and the amount of dynamically supported topography; up to 50 km of convergence has been accomodated by flexure forming ridges and troughs. A continuous, strike slip fault accomodates oblique convergence along the length of the boundary. Where angles of convergence are highest (>20o ), underthrusting is observed in addition. Gravity modeling and seismicity suggest ~50 km of underthrusting in the southern Hjort Trench, but only define an eastwardly dipping Australian slab to about 20 km depth. Lithosphere underthrust in the southern trench is translated subparallel to the ~N-trending boundary, limiting the eastward extent of underthrust slab. Reconstructions of the plate boundary since 33.3 Ma show that the Antarctic-Australian-Pacific triple junction migrated southward with respect to the Australian plate resulting in the present day curved plate boundary. Migration resulted in lengthening of the dextral transform fault connecting the Macquarie Ridge and Southeast Indian Ridge spreading centers and shortening of the easternmost ridge-segment of latter spreading center. The MRC in the Hjort region changed from a dextral transform into an obliquely convergent zone of incipient subduction. Geological Sciences